The behavioral approaches of entrepreneurial characteristics in Madura - Mohammad Arief (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
The number of Small and Medium Enterprises (SMEs) factually increased in recent years due to several factors such as the imbalance between demand and supply for the workplace. According to various literature study, entrepreneurs are related to the individuals' capacity and characteristics in exploiting market opportunities. The previous studies showed that entrepreneurs need to determine individual characteristics for proceeding with other strategies. Therefore, there are particular characteristics related to business activities that need to be possessed by prospective entrepreneurs. This research aims to reveal the entrepreneurship characteristics with a behavioral approach. Data were collected from 5 entrepreneurs in Bangkalan Regency using the purposive sampling technique. The result showed that entrepreneurial behaviors are either active or passive. In addition, the existence of competitors is not considered a threat to independence in developing business ideas.